Poverty, Eschatology and the Medieval Church
1 online resource (512 pages)
Keywords: This volume is a collection of essays written in honor of David Burr, emeritus professor at the Polytechnic University of Virginia (Blacksburg): a scholar who has spent a career researching and publishing on the multi-faceted phenomenon of the Spiritual Franciscans (late 13th-early 14th century) and, in particular, on the life and writings of Peter of John Olivi in southern France. Representing some of the finest scholars in the field these eighteen scholarly essays touch on aspects of both phenomena. Three essays are devoted to the historiography of David Burr; three are dedicated to medieval Apocalypticism; another seven deal specifically with Peter of John Olivi; and five final essays explore aspects of the Spiritual Franciscans, their precursors and adherents. Contributors are C. Colt Anderson, Marco Bartoli, Michael F. Cusato, Gilbert Dahan, Alberto Forni, Fortunato Iozzelli, Philip D. Krey, Robert E. Lerner, Warren Lewis, Michele Lodone, Kevin Madigan, Antonio Montefusco, Delfi I. Nieto-Isabel, Dabney G. Park, Sylvain Piron, Gian Luca Potestà, Marco Rainini, and Paolo Vian.